Amplitude and frequency variability of the pulsating DB white dwarf stars KUV 05134+2605 and PG 1654+160 observed with the Whole Earth Telescope - Handler, Gerald (2003)
We have acquired new time series photometry of the two pulsating DB white dwarf stars KUV 05134+2605 and PG 1654+160 with the Whole Earth Telescope. Additional single-site photometry is also presented. We use all these data plus all available archival measurements to study the temporal behaviour of the pulsational amplitudes and frequencies of these stars for the first time. We demonstrate that both KUV 05134+2605 and PG 1654+160 pulsate in many modes, the amplitudes of which are variable in time; some frequency variability of PG 1654+160 is also indicated. Beating of multiple pulsation modes cannot explain our observations; the amplitude variability must therefore be intrinsic. We cannot find stable modes to be used for determinations of the evolutionary period changes of the stars. Some of the modes of PG 1654+160 appear at the same periods whenever detected. The mean spacing of these periods (≈40 s) suggests that they are probably caused by non-radial gravity-mode pulsations of spherical degree l = 1. If so, PG 1654+160 has a mass around 0.6Mʘ. The time-scales of the amplitude variability of both stars (down to two weeks) are consistent with theoretical predictions of resonant mode coupling, a conclusion which might however be affected by the temporal distribution of our data.